PENGEMBANGAN ELEKTRONIK LEMBAR KERJA PESERTA DIDIK BERBASIS PROJECT BASED LEARNING PADA MATERI BENTUK MOLEKUL - Ulfa Sapriyanti; Husna Amalya Melati; Lukman Hadi (Universitas Tanjungpura, Prodi Pendidikan Kimia, 2020)
The aims of this research were to determine the feasibility of Development Electronic Worksheet (e-worksheet) based on Project Based Learning on geometry molecule by the results of expert judgments and student responses on the results of field trials. The form of this research is research and development (R&D) which adopts Kemp's development model. The subject of this research was Electronic Worksheet (e-worksheet) based on Project Based Learning on geometry molecule which was tested at 27 students of SMAN 10 Pontianak. The instruments of data collections were the feasibility questionnaire and student response questionnaire. The results of data processing showed that the e-worksheet that developed was suitable for use in learning in terms of the percentage of content material, presentment, linguistic, and media respectively 96.6%; 96.8%; 90.2% and 86.1%. The result percentage of the calculation student questionnaire responses to the material aspects was 83.33%, 79.31% to linguistic aspects and graphical aspects was 89.50%. Based on the average of the three aspects of student responses, it was found that the percentage of e-worksheet based on Project Based Learning on geometry molecule subject was 84.04%, which was included in the very high category.